(untitled) (CIPEEX, 2025)
The strangeness with new technologies is viewed through different lenses of modernity, some of which take the form of strangeness and denial due to distrust towards innovation Using an analytical approach, issues related to cybersecurity, digital accessibility, trust in financial institutions, and individual preferences are examined Through a critical analysis of literature, based on theoretical foundations from journals sourced from sites such as SciELO and Google Scholar, it is noted that several factors contribute to this resistance Brazilians are concerned about the security of online transactions, driven by an increase in cyber fraud and scams. This mistrust affects the decision to adopt online banking services, leading many to stick to traditional methods and miss out on the benefits of new technologies Lack of internet access is also a significant obstacle, especially among vulnerable groups such as the elderly and people with disabilities The complexity and lack of adaptation to their specific needs make it difficult for these groups to use online banking services Additionally, trust in financial institutions is a crucial aspect Many Brazilians hesitate to share personal and financial information online due to lack of transparency and concerns about data protection. Finally, individual preferences play an important role in the decision not to adopt financial apps; some people value human contact and the convenience of in-person transactions, choosing to avoid online banking services In summary, the non-adoption of internet banking in Brazil is influenced by a variety of factors, including security concerns, accessibility, trust, and personal preferences These considerations stem from a lack of organizational and promotional structure, directly contributing to the rejection of online banking services and the technological exclusion process.